Synthesis and antibacterial activity of composite based on chitosan-grafted-(n-butyl acrylate) and silver nanoparticles - Ha, La Thi Thai; Mai, Chau Ngoc (Vietnam Journal of Science and Technology, 2019)
It has been found for a long time that chitosan (CS) and silver nanoparticles (AgNPs) have outstanding antibacterial activities but there were some drawbacks restricting their wide utilization. In this research, CS modified is combined with AgNPs to expand applications and enhance the antibacterial activities. The colloid of CS and AgNPs (CS/Ag) was synthesized via chemical reduction while grafting copolymerization was carried out with monomer n-butyl acrylate (BA) and initiator tert-butyl hydroperoxide (TBHP) generating composite between CS-g-BA/Ag. The effects of parameters on synthesizing CS-g-BA/Ag composite were studied by determining the grafting percentage (G%) and grafting efficiency (E%).